Materia frágil poéticas para el siglo XXI en América Latina y España - Martínez, Erika (Colección Letral, 2020)
How are the words and bodies arranged in the poem? How do they come into contact from their latitude, longitude and depth, from the verbal substance that defines them? Fragile matter: poetics for the 21st century in Latin America and Spain aspires to answer these questions through various approaches to current poetry, taking into account the limits, conflicts and new conditions of possibility of our being in common. To do so, several studies are proposed on the dissident aesthetics that are making their way on both sides of the Atlantic, on the latest performative drifts of lyrical discourse and the implications of our growing transmediality. Added to them is a series of inquiries about the poets of the 21st century and their intervention of the word through proposals that disturb the structure of the intimate and the collective, sexual identity or the family, provoking alternative forms of subjectivity. Starting from different national, cultural and historical horizons, these essays analyze the politics of the common, understood as a symbolic and material practice that runs through poetic discourse. They explore their space for emancipation and their work with the new articulations of violence. They think of poetry and its fragility as a condition for resistance.